Venetoclax as a cytoreduction therapy option for acute promyelocytic leukemia in newly diagnosed adult patients: a case report of a 35-year-old female with schizophrenia - Wang, Lingling; Miao, Yuqing; Cheng, Yuexin (Frontiers in Oncology, 2025)
Venetoclax is effective in treating relapsed acute promyelocytic leukemia (APL), newly diagnosed pediatric APL, variant APL, and APL with central nervous system involvement. In newly diagnosed adult APL, venetoclax is rarely used. Herein, we present a case of newly diagnosed adult APL in a 35-year-old female with schizophrenia who received venetoclax as a cytoreduction therapy option. The patient was admitted with myocardial ischemia, the cardiac ultrasound indicating left ventricular ejection fractions (EF) of 44%, a 17-year history of schizophrenia, treated with ziprasidone, lorazepam, and clozapine. She developed differentiation syndrome (DS) shortly after receiving All-trans-retinoic acid (ATRA) and arsenic trioxide (ATO) and experienced heart arrest. In the occurrence of DS, this young female encountered numerous therapeutic conundrums, including cytoreduction of hydroxyurea being ineffective, the potential psychological worsening caused by dexamethasone use, and the cardiotoxicity of anthracyclines. We administered venetoclax 20 mg once daily as a cytoreduction therapy. The white blood cells (WBC) dropped from 72.16×109/L to 5.19×109/L in 4 days, and the proportion of promyelocytes in the peripheral blood smear decreased from 78% to 10%. Tumor lysis syndrome (TLS) did not develop since the patient received good supportive treatment. For newly diagnosed adult patients with APL who are unresponsive to traditional cytoreduction therapy, venetoclax can be an effective option.